Measuring Factors of Trust in the Use of E-Government: A Multi-Factor Analysis of the E-Government in Indonesia - Altino, Iqbal Caraka; Sudarto, Reska Nugroho; Sensuse, Dana Indra; Lusa, Sofian; Putro , Prasetyo Adi Wibowo; Indriasari , Sofiyanti; Brillianto, Bramanti (Ikatan Ahli Informatika Indonesia (IAII), 2025)
The implementation of dynamic records management applications within the Indonesian government remains relatively limited, with a lack of comprehensive integration between authorised institutions at both the central and regional levels. This research examines the impact of technical aspects, government agency variables, citizen variables, and risk indicators on trust in e-government. Furthermore, this study seeks to establish the effect of social factors and the advantages of trust in e-government. Finally, this research shows how trust in e-government influences satisfaction, willingness to use, and acceptance of e-government. The study examined 117 respondents using the integrated dynamic archival information system - SRIKANDI. Technical and risk factors were found to positively influence trust in e-government, with effects on satisfaction, intention to use, and adoption of e-government. Those who trusted SRIKANDI were more likely to utilize and implement the program. The findings indicate that for civil servants, trust in the government is also a factor influencing the utilisation of e-government services.